Project-based learning (PjBL) strategies with gamification - Putri Fadilla Azzahra Fazarini; Yerry Soepriyanto; Henry Praherdhiono (Inovasi Kurikulum)
This research aims to develop and test the effectiveness of the Project-Based Learning (PjBL) learning model integrated with gamification (G-PJBL) to increase student engagement and learning outcomes in Graphic and Visual Media courses. The background to this research is the low graduation rate of students in this course due to the diverse backgrounds and abilities of students. PjBL research with Gamification activities uses the ASSURE development model, which contains six stages. Construction is carried out sequentially according to the plans that have been made. Research data was obtained from validation by learning design experts, observations during learning, and student learning outcomes. The development of PjBL with gamification activities has had a positive impact on increasing student engagement and motivation. The research results show that the well-structured G-PJBL syntax follows student needs. Validation by learning design experts shows that the learning design is feasible. In addition, the research results show that G-PJBL can increase student engagement and learning motivation and improve their learning achievement. This model can be applied to other courses that require student involvement and creativity.